ANALISA PENGARUH WAKTU PENCUCIAN 5% NAOH DAN PELAPISAN ACRYLIC TERHADAP KEKUATAN TARIK DAN IMPAK PADA KOMPOSIT SERAT KENAF MATRIK RESIN POLYESTER - Widodo, Basuki; Widodo, Feri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
Composite material especially with fiber reinforcement starts growing rapidly with existence of requirement of light and strong material. Beside that, it is easy to be formed and resistant to corrosion. In this last decade, composite material using natural fiber has been implemented by the European automobile producers. Based on those considera-tions research about composite using kenaf fiber as reinforcement material big strength of mechanic for each varation. (1) Kenaf fiber without cleaning, (2) Kenaf fiber with soaking in NaOH for an hour,(3) Kenaf fiber with soaking in NaOH for two hours and with material matrix polyester.Based on the calculation and experimental analysis soaking in NaOH and bedding of Acrylic increase the mechanical properties. So composite resin polyester as matrix with treatment is much better than without treatment.